Solitary angiokeratoma on palms and soles: A clinicopathological analysis of 21 cases. Issue 8 (5th June 2013) - Wang, Lei; Gao, Tianwen; Wang, Gang
Abstract: Angiokeratoma includes a group of unrelated diseases characterized by hyperkeratosis and dilation of vessels in the superficial dermis. In this study, 21 cases of solitary lesions located on palms and soles and histopathologically diagnosed as angiokeratoma were analyzed retrospectively. All lesions presented as red to violet macules or plaques. Histopathologically, all of them showed hyperkeratosis and vascular dilation in the papillary to deep dermis. The elongated vessels were of different sizes and shape, lined by a single layer of endothelial cells. In 13 lesions, the endothelial cells protruded into the lumen, forming a hobnail appearance. Immunohistochemical study showed the endothelial cells were positive for CD31 and CD34, negative for D2‐40, and focally positive for Wilms tumor 1 (WT‐1) in most cases. Our cases represented a rare type of angiokeratoma located on the palms and soles, in which the focal positivity of WT‐1 was different from previously reported vascular proliferations.